Manajemen Pembiayaan Sarana Dan Prasarana Di Madrasah Tsanawiyah Ishlahul Amanah Kecamatan Pangalengan - Badrudin,, Badrudin,; Nurcholis, Muhammad; Setiawan, Iwan; Misbahudin, Misbahudin; Sudrajat, Entik (GEMA EKONOMI, 2023)
Management of facilities and infrasructure in private school, especially madrasa, is a strategic action that determines the future sustainability of institution. Both in terms of quality and quantity of students. The number of private junior high school-level school in Indonesia reached 41.70% or 16,967. The problem faced by private school is the availability of education facilities and infrastructure. Private educational institution, especially madrasas, strive to provide adequate educational facilities and infrastructure amid limitations. This is different from state schools are financed from state finansial sources through the APBN, APBD or DAK (special allocation fund). Even if these three sources are fullfiled, the procurement of advice and infrastructure will not only include basic facilities such as classroom, laboratory or libraries, bur also support supporting facilities such as halls, canteens or multimedia and art rooms. MTs Ishlahul Amanah Pangalengan distric, is a private madrasa in Pangalengan Distric, Bandung Regency, with the priciples of management of facilities and infrastructure financing that firmly holds the principles of accountability and transparency, supported by effective communication style, succesfully developed the educational institution to became accredited A, number of students is approaching 700, 20 groups and complete supporting facilities. This study tries to describe and di gup information on how the management function is carried out by the institution so that it has strong enough funding, so madrasa is progressing and developing and slowly into a profitable institution. The research was conducted qualitively through interviews, observations and document sudies. The conclusions in this study indicate that the three things that maket his institution succesfully managing funds from the community in this case parents of students are effective communcation from stake holder, especially the school committee, accountability in financing management and transparency in development activities